The cytotoxic and the biological (antibacterial and antifungal) activities of Centaurea iberica and Ferulago confusa - (:unkn) unknown (My University, 2001)
The petroleum ether:ether:ethanol (1:1:1) extract of the aerial parts of Centaurea iberica (Asteraceae) (23.3536 g)1 and the petroleum ether and ethanolic extracts of the fruits of Ferulago confusa (Apiaceae) (14.232 g; 19.530 g) show cytotoxic effect by the Brine Shrimp (Artemia Salina) lethality bioassay and antibacterial and antifungal activities were tested by the agar well diffusion and dilution methods. In conclusion, the most effective extracts against P.aeruginosa and E.coli were found to be the ones obtained from C.iberica compared with Ampicillin. C.iberica has been found effective against only one strain of C.guilliermondii; The ethanolic extract of F.confusa has been found effective against C.guilliermondii and C.glabrata compared with Fluconazole.
Keywords: Antibacterial activity; Antifungal activity; Apiaceae; Asteraceae; Brine shrimp; Centaurea iberica; Ferulago confusa